VISION, KNOWLEDGE, POWER: EROWID.ORG AND THE “TRIP REPORT” - Witte, John James (AoIR Selected Papers of Internet Research, 2015)
The invention of LSD in 1938, and its eventual discovery as a psychoactive agent in 1943, spawned decades of debate and experimentation among intellectual dissidents in America and Europe. It’s spawned at least one literary genre: the “trip report”. From Albert Hoffman’s first account of his legendary bicycle ride, to the writings of drug luminaries like Timothy Leary and Aldous Huxley, trip reports have striven to describe the indescribable. They’ve provided guidance to those curious about psychedelia, and they’ve provided a forum for drug users to document their personal revelations. The genre has, in fact, become one of the sturdiest and most common types of writing on the Internet. Whole sections of older communities like WELL and Usenet arededicated to the posting of trip reports, and the tradition has continued onto newer forums like Reddit and 4chan. It’s from this discursive context that the website Erowid.org emerged. Referred to as “the Wikipedia of drugs”, Erowid stepped in to the role of the medical expert by providing reliable medical and legal advice to those interested in mind-altering substances. The Erowid archive represents an underanalyzed area of media research for a number of reasons. Through a close reading of this singular genre of new media cultural production, and, specifically, the archive accessible through erowid.org, I hope to theorize some of the peculiarities of writing on the Internet, writ large.